Two new genera of the bee tribe Lonchopriini, with additional taxonomic notes (Apidae, Colletinae) - Melo, Gabriel A. R. (Acta Biológica Paranaense, 2021)
Two new genera are proposed in Lonchopriini, a tribe of the neopasiphaeine line in the Colletinae. The new genus Camposapis (type-species: Leioproctus larejae Compagnucci & Roig-Alsina, 2008) is proposed to accommodate a distinct lineage from Argentina and Brazil. The new genus Silveirapis (type-species: Lonchopria robertsi Michener, 1989) is proposed for a lineage previously placed in Biglossa sensu Michener, but which came out as sister-group of Ctenosibyne Moure based on molecular evidence. In addition, Biglossidia solanophila is proposed as a replacement name for Rhinetula chalybaea Friese, 1922 due to homonymy with Biglossidia chalybaea (Friese, 1906). Lectotype designations are also proposed for Biglossa thoracica Friese, 1906 and Biglossa chalybaea Friese, 1906.